Using developmental research to design innovative knowledge translation technology for spinal cord injury in primary care: Actionable Nuggets™ on SkillScribe™ - Smith, Karen M. (Maney Publishing, 2014)
CONTEXT/OBJECTIVE: Actionable Nuggets™ for spinal cord injury (SCI) are a knowledge translation tool facilitating evidence-based primary care practice, originally developed in 2010 and refined in 2013. Evaluation results from these two phases of development have informed the design of SkillScribe™, an innovative electronic platform intended to offer reflective continuing medical education (CME) programming through mobile devices in order to support the key features of the Actionable Nuggets™ approach. This brief article describes the ongoing development of Actionable Nuggets™ for SCI on SkillScribe™ by: (1) summarizing the work to date on Actionable Nuggets™; (2) describing evaluation results of Actionable Nuggets™; (3) placing SkillScribe™ in the context of adult education. DESIGN: Developmental Research Design. SETTING: Canadian primary care. PARTICIPANTS: Primary care physicians; specialist physicians. INTERVENTIONS: Twenty educational modules on SCI. OUTCOME MEASURES: Pre- and post-test knowledge survey, feedback and use statistics, impact assessment survey, qualitative analysis of evaluation data. RESULTS: In both hard copy and electronic form, physicians report that Actionable Nuggets™ are an acceptable and useful approach to providing CME for low-prevalence, high-impact conditions like SCI. The key elements of this tool are that they: offer evidence-based information in small, focused “nuggets”; position information where physicians most frequently seek it; offer information in a format that permits direct translation into action in primary care; allow time for reflection; attach practice tools; and offer CME credit. CONCLUSION: Actionable Nuggets™ for SCI, delivered using a convenient and portable electronic medium, with time-released content and interactive testing has the potential to improve the primary care of patients with SCI.